2017
DOI: 10.1186/s12913-017-1998-5
|View full text |Cite
|
Sign up to set email alerts
|

Rate and associated factors of non-retention of mother-baby pairs in HIV care in the elimination of mother-to-child transmission programme, Gulu-Uganda: a cohort study

Abstract: BackgroundPoor retention in HIV care of mother-baby pairs remains a public health challenge in the elimination of mother-to-child transmission (eMTCT) of HIV. We determined the rate of non-retention and time to non-retention of mother-baby pairs and associated factors in Gulu district, Northern Uganda.MethodsMother-baby pairs enrolled into the eMTCT programme at Gulu Regional Referral Hospital (GRRH) and Lacor Hospital (LH) were retrospectively followed for 18 months. The primary outcomes were the rate of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 24 publications
5
26
2
Order By: Relevance
“…A retrospective follow-up study at different public health facilities in Northeast regions of Ethiopia showed that cumulative incidence LTFU was 16.5% (29). Similar nding also revealed that cumulative incidence of LTFU was 15.4% with incidence rate of 9 per 1000 person-months in western Ethiopia (30) and 18.2% in Southern Ethiopia (31).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…A retrospective follow-up study at different public health facilities in Northeast regions of Ethiopia showed that cumulative incidence LTFU was 16.5% (29). Similar nding also revealed that cumulative incidence of LTFU was 15.4% with incidence rate of 9 per 1000 person-months in western Ethiopia (30) and 18.2% in Southern Ethiopia (31).…”
mentioning
confidence: 67%
“…Another retrospective cohort study in Myanmar showed that pregnant women's LTFU rate was 7 per 1000 person-years under option B+ PMTCT programs (11). A retrospective follow-up study in different African countries showed that the incidence of LTFU among pregnant and lactating mothers under option B+ program were still high which ranges from 16% to 53.7 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Previous studies in Ethiopia showed that the rate of LTFU among women under Option B+ program varied region to region.…”
mentioning
confidence: 99%
“…By 2016, the Ministry of Health estimated that 92% of HIV-positive pregnant women were initiated on ART 1 but only 74% of those women were retained in HIV care at 12 months postpartum 2 . Studies done elsewhere have documented similar rates of Loss-To-Follow-Up (LTFU) in HIV care [3][4][5][6][7][8][9] . LFTU breastfeeding mothers, who therefore are not adhering to ART, are at high risk of transmitting HIV to conducted in Mangochi and Salima districts, in Southern and Central Malawi, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In Togo in 2011, 157 HIV-exposed children (34.5%) were considered lost to follow-up prior to PCR-1 in a study on the accessibility of EID at Lomé, another 100 (21.9%) were also loss between the completion of PCR-1 and the results of this review, an overall loss of 257 (56.6%) [5]. In Uganda, nearly one third of mother-baby pairs are not retained in HIV care: lack of EID services, poor quality service, non-disclosure of mother's HIV status and understanding the importance of adhering to all appointments together with the baby, were associated with time to non-retention [6]. EID is one of the strategies to achieve UNAIDS (Joint United Nations Programme on HIV/AIDS) goals 90-90-90 (by 2020, 90% of all people living with HIV will know their status, 90% of all people diagnosed with HIV will receive a supported antiretroviral therapy (ART) and 90% of all people receiving ART will have a lasting viral suppression); however, country data for this indicator are fragmented or non-existent [7][8][9][10].…”
Section: Why Early Diagnosismentioning
confidence: 78%